Peran Generasi Guru Dalam Membangun Antusiasme Belajar Siswa Generasi Alpha di SD ST Bellarminus Bekasi - Yuliawati, Alit; Simbolon, Bintang; Limbong, Mesta; Tampubolon, Manahan (Jurnal Ilmiah Global Education, 2025)
Education plays a strategic role in shaping a high-quality future generation, with teachers serving as the primary facilitators of learning. The generational diversity among teachers creates variations in teaching styles that can influence student learning enthusiasm, particularly for Generation Alpha, who are characterized as digital natives. This study aims to understand the differences in teaching styles based on teacher generations and their implications for the learning enthusiasm of Generation Alpha students at St. Bellarminus Elementary School in Bekasi. A qualitative method with a case study approach was used, involving in-depth interviews, classroom observations, and documentation. The findings reveal that older generation teachers tend to use conventional lecture-based methods, while younger generation teachers are more adaptive to technology and interactive approaches. A mismatch between teaching styles and the characteristics of Generation Alpha students can affect their level of engagement and enthusiasm in learning. Therefore, more innovative and student-centered teaching strategies are needed to enhance the effectiveness of instruction.